MANAJEMEN KEUANGAN UMKM: LOVE OF MONEY, INKLUSI KEUANGAN, DAN FINANCIAL SELF EFFICACY - Fany Dwiyanti Adinda; Kurniawan, Moh. Zaki; Safrizal, Helmi Buyung Aulia (MANAJEMEN DEWANTARA, 2024)
In Indonesia, a large number of MSMEs have not yet implemented efficient financial management techniques. The financial management of MSMEs in Pamekasan Regency is examined in this study in relation to financial inclusion, financial self-efficacy, and a Love of money. Purposive sampling and other non-probability sampling techniques were used in a quantitative approach. Researchers investigated variable relationships using four analytical approaches: multiple regression analysis, data quality assessment, standard assumption verification, and hypothesis testing. The results show that while financial inclusion and financial self-efficacy do not have a partial impact on financial management, a Love of money does. However, the financial management of MSMEs in Pamekasan Regency is simultaneously impacted by these three factors.